2022
DOI: 10.1039/d1sc04779e
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate sodalite zeolitic imidazolate frameworks: a direct solvent-free synthesis

Abstract: Different mixed-ligand Zeolitic Imidazolate Frameworks (ZIFs) with sodalite topology, i.e. isoreticular to ZIF-8, unachievable by conventional synthetic routes, have been prepared using a solvent-free methodology. In particular, the versatility of...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…28 However, in this case, the authors were not able to obtain cell parameters, or atomic positions within this previously unknown structure. The qtz-[Zn(mIm) 2 ] has some differences to other previously published qtz topology ZIFs, qtz-[M(eIm) 2 ] where M = Zn,29 Fe and Co, 27 and [Fe(mIm) 2 ]. 30 Both qtz-[Fe(mIm) 2 ] and qtz-[M(eIm) 2 ] possess one unique M equivalent position, whilst qtz-[Zn(mIm) 2 ] has three distinct Zn atomic positions each with a distorted tetrahedral environment (Fig.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…28 However, in this case, the authors were not able to obtain cell parameters, or atomic positions within this previously unknown structure. The qtz-[Zn(mIm) 2 ] has some differences to other previously published qtz topology ZIFs, qtz-[M(eIm) 2 ] where M = Zn,29 Fe and Co, 27 and [Fe(mIm) 2 ]. 30 Both qtz-[Fe(mIm) 2 ] and qtz-[M(eIm) 2 ] possess one unique M equivalent position, whilst qtz-[Zn(mIm) 2 ] has three distinct Zn atomic positions each with a distorted tetrahedral environment (Fig.…”
mentioning
confidence: 68%
“…26 Surprisingly, the qtz -ZIF-8 material has only been achieved in the presence of the eIm linker, where eIm = 2-ethyl imidazolate (C 5 H 7 N 2 ) − . 27 In an incredibly recent study, a material exhibiting the qtz topology was prepared by heating a sample of nanosized (20 nm) crystalline SOD-[Zn(mIm) 2 ] . 28 However, in this case, the authors were not able to obtain cell parameters, or atomic positions within this previously unknown structure.…”
mentioning
confidence: 99%
“…Generally, a greater ratio of bim À is found in the framework than was used in the synthesis, which we hypothesize is due to the combined bulkiness of 2M56DFbim À and the electron withdrawing of the fluorine atoms which reduces the charge density on the imidazolate nitrogens. 26 The resulting frameworks were activated under dynamic vacuum at 150 1C for 16 h. Complete solvent removal was confirmed for all frameworks using post-digestion 1 H NMR spectroscopy (Fig. S17-S22, ESI †), except for the 5 : 4 (indicates ratio of bim À to 2M56DFbim À linkers) framework, which effectively traps E0.02 equivalents of DMF per linker in the activated structure.…”
mentioning
confidence: 87%
“…Generally, a greater ratio of bim − is found in the framework than was used in the synthesis, which we hypothesize is due to the combined bulkiness of 2M56DFbim − and the electron withdrawing of the fluorine atoms which reduces the charge density on the imidazolate nitrogens. 26…”
mentioning
confidence: 99%
“…Recently, Cabrelles et al demonstrated that hybrid ZIFs containing multivariate ligands (2-methylimidazole, 2-methylbenzimidazole, and 2-ethylimidazole) could be synthesized in situ via a solvent-free methodology. [23] However, the direct solution-based synthesis of multivariate ZIFs has not yet been reported owing to disturbances in the SOD topology.…”
Section: Introductionmentioning
confidence: 99%